Managing Multicultural Islamic Education through Conflict Resolution Learning Development in Indonesia - Thoyib, Muhammad; Subandi, Subandi; Harsoyo, Roni (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Along with the frequent social conflicts in Indonesia, the multicultural reality of this country is becoming increasingly urgent to be reconstructed so that it can become an "integrating force" for the future of this nation, especially through the education sector. In that context, Madrasah Ibtidaiyah Nahdlatul Ulama (MINU) Bangil Pasuruan, East Java, is a "lantern" for Indonesia's future multiculturalism that has implemented multicultural education management well. It involves various religious and ethnic cultural organizations, such as NU, Muhammadiyah, and others. Also, there are several ethnic groups like Javanese, Sundanese, Madurese, and Chinese. This qualitative research with a phenomenological approach-case study attempts to analyze the implementation of multicultural education management to develop conflict resolution learning at MINU Bangil Pasuruan. This research shows that the application of multicultural education management is running well with the main learning models based on visiting culture class learning. Meanwhile, the impact of multicultural education management includes 1) the life and interpersonal relationships of the entire academic community and the environment of educational institutions becoming more harmonious and inclusive, despite the ethnic plurality in the community; and 2) the learning process becomes more enjoyable and effective because it is supported by the growing sense of belonging and love between teachers and students.